Concurrent use of rabacfosadine and L‐asparaginase for relapsed or refractory multicentric lymphoma in dogs. (16th February 2020) - Cawley, Jacob R.; Wright, Zachary M.; Meleo, Karri; Post, Gerald S.; Clifford, Craig A.; Vickery, Kathryn R.; Vail, David M.; Bergman, Philip J.; Thamm, Douglas H.
Abstract: Background: Rabacfosadine (RAB), a novel antineoplastic agent conditionally licensed for the treatment of lymphoma in dogs, is efficacious in both naïve and previously treated dogs. Its use in combination with L‐asparaginase (L‐ASP) has not been studied. Hypothesis/Objectives: To evaluate the safety and efficacy of L‐ASP given concurrently with RAB in dogs with relapsed multicentric lymphoma. Animals: Fifty‐two dogs with relapse of lymphoma after treatment with at least 1 doxorubicin‐based chemotherapy protocol. Methods: Open‐label, multicenter, prospective single‐arm clinical trial. Dogs were treated with RAB at 1.0 mg/kg IV every 21 days for up to a total of 5 doses. L‐asparaginase was administered at 400 IU/kg SQ concurrently with the first 2 treatments of RAB. Results: The overall response rate (ORR) for all dogs was 67%, with 19 dogs (41%) achieving a complete response (CR). The median progression‐free survival time (MPFS) was 63 days (range 5‐428 days). Dogs experiencing a CR as their best response had an MPFS of 144 days (range 44‐428 days). Adverse events were similar to previous studies evaluating single agent RAB. Failure to achieve a CR and having previously received L‐ASP were negative prognostic factors on multivariate analysis. Conclusions and Clinical Importance: Concurrent RAB/L‐ASP appears to be both efficacious and safe for treating relapsed multicentric lymphoma in dogs. Adverse events were most often mild and no unexpected toxicoses were observed.